The role of supervisor work-life support on the correlation between work autonomy, workload and performance: perspective from Tanzania banking employees - Mwanaidi Shafii Msuya; Anitha Bommagowni Kumar (Future Business Journal, 2022)
Abstract This research aims to assess the influence of supervisor work-life support on bank employees' performance linking work autonomy and employee workload in this relationship. A survey was conducted among bank employees in the Central Zone regions of Tanzania. Bank workers completed 417 survey questionnaires in total. The data was then analysed using structural equation modelling. The researchers use Smart PLS, a data analysis tool, to see if there are any theoretically supported connections between variables of interest. SPSS, on the other hand, handled data coding and descriptive statistics. The study results revealed that work autonomy mediated significantly the association among supervisor work-life support and work performance. Contrary to expectation, the linking of workload in the correlation between supervisor work-life support and work performance was negative and insignificant. Moreover, work autonomy and workload significantly influence bank employees’ job performance in this study. Similarly, the study findings indicated that supervisor work-life support positively impacts employee performance. The study has important implications for managers since it improves understanding of the strengths of their organizations' work-life practices. Such as workload and work autonomy when linked with supervisor work-life support on influencing employee job performance and developing new strategies that may enhance employee's well-being. Again, the findings imply that there should be supportive work-life practices that moderate the balance between home and work realms to attain effective organizational performance.